(untitled) (Archaeologia Adriatica, 2025)
Within the boundaries of Bosnia and Herzegovina, very few Lasinja-culture sites have been identified. The area has thus been categorised as a peripheral Lasinja-culture distribution zone. To date, Lasinja pottery characteristics have been confirmed at seven sites in Bosnia and Herzegovina: Zemunica in Radosavska near Banja Luka, Visoko Brdo in Lupljanica, Vis in Modran near Derventa, Donji Klakar near Bosanski Brod, Gornja Tuzla in Tuzla, Biograd in Prusac near Donji Vakuf and Cazin’s Old Town. This paper presents the find of a miniature Lasinja-culture bottle from the Visoko Brdo site in Lupljanica near Derventa, confirming the importance of renewed excavations as well as of analysing Lasinja-culture finds from past excavations.